Involvement of the millennial generation in boosting the digital economy in the era of society 5.0: literature study - Sigit Purwoko (Gema Wiralodra, 2023)
The purpose of this research is to find out how the involvement or role of the millennial generation is in boosting the digital economy in the era of society 5.0. This research method uses a literature review study by searching for articles using search engines such as EBSCO, ScienceDirect, and Proquest. Articles were searched using "Millennials, the digital economy and the era of society 5.0. The criteria for the articles used were those published in 2012-2022. Based on the articles collected, it was found that every year, Indonesia's digital economy is Increasing. The sector that plays the most role is e-commerce, with a value of USD 59 billion in 2022. This is in line with Indonesia's increasing number of internet users, numbering 210.03 million, and most users are millennials, which involves assisting the government in encouraging economic growth through entrepreneurial activities. However, in the process, the millennial generation still faces various challenges. Various parties, especially the government, are needed to assist and provide facilities to the millennial generation to develop themselves into more significant business actors.